Two Ways of High-Energy Heavy Ion Interactions: Spallation and Burst - Brandt, Reinhard; Ditlov, Valery; Haiduc, Maria; Firu, Elena; Neagu, Alina Tania; Ganssauge, Eberhard; Nezhad, Reza H.; Westmeier, Wolfram (Scientific research, 2015)
A new approach to solving the observation of enhanced neutron production in high-energy heavy ion induced reactions in thick targets is presented. Two different reaction mechanisms in these interactions are considered: 1) Limited fragmentation of the projectile, called SPALLATION; 2) Complete nuclear fragmentation of the projectile fragment into individual relativistic hadrons only, referred to as “BURST”. The abundance of this second path increases with the charge and energy of the projectile and may be responsible for enhanced neutron production observed with radiochemical methods in 44 GeV 12C and 72 GeV 40Ar irradiations. Interactions of 72 GeV 22Ne in nuclear emulsions show that SPALLATION and BURST have strongly different interaction signatures, and also that the rate of BURSTS increases from (26 ± 3)% of all interactions in the 1st generation to (78 ± 6)% in the 2nd generation. Further experimental signatures of BURSTS will be described; however, no model based on physics concepts can be presented. This effect may have practical consequences for neutron safety considerations in the construction of advanced heavy ion accelerators
Keywords: Thick Target; High Energy Projectile; Unresolved Problems; BURST